Prospects for using Entomopathogenic Nematodes as a biocontrol agent against Western flower thrips Frankliniella occidentalis (Thysanoptera: Thripidae) - Dlamini, Thandwa (Stellenbosch : Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.